Acute subjective effects in LSD- and MDMA-assisted psychotherapy. (April 2021) - Schmid, Yasmin; Gasser, Peter; Oehen, Peter; Liechti, Matthias E
Background: Lysergic acid diethylamide (LSD) and 3, 4-methylenedioxymethamphetamine (MDMA) were used in psychotherapy in the 1960s–1980s, and are currently being re-investigated as treatments for several psychiatric disorders. In Switzerland, limited medical use of these substances is possible in patients not responding to other treatments (compassionate use). Methods: This study aimed to describe patient characteristics, treatment indications and acute alterations of mind in patients receiving LSD (100–200 µg) and/or MDMA (100–175 mg) within the Swiss compassionate use programme from 2014–2018. Acute effects were assessed using the 5 Dimensions of Altered States of Consciousness scale and the Mystical Experience Questionnaire, and compared with those in healthy volunteers administered with LSD or MDMA and patients treated alone with LSD in clinical trials. Results: Eighteen patients (including 12 women and six men, aged 29–77 years) were treated in group settings. Indications mostly included posttraumatic stress disorder and major depression. Generally, a drug-assisted session was conducted every 3.5 months after 3–10 psychotherapy sessions. LSD induced pronounced alterations of consciousness on the 5 Dimensions of Altered States of Consciousness scale, and mystical-type experiences with increases in all scales on the Mystical Experience Questionnaire. Effects were largely comparable between patients in the compassionate use programme and patients or healthy subjects treated alone in a research setting. Conclusion: LSD and MDMA are currently used medically in Switzerland mainly in patients with posttraumatic stress disorder and depression in group settings, producing similar acute responses as in research subjects. The data may serve as a basis for further controlled studies of substance-assisted psychotherapy.